Flapping Peryleneimide as a Fluorogenic Dye with High Photostability and Strong Visible‐Light Absorption. (15th July 2020) - Kimura, Ryo; Kuramochi, Hikaru; Liu, Pengpeng; Yamakado, Takuya; Osuka, Atsuhiro; Tahara, Tahei; Saito, Shohei
Abstract: Flapping fluorophores (FLAP) with a flexible 8π ring are rapidly gaining attention as a versatile photofunctional system. Here we report a highly photostable "flapping peryleneimide" with an unprecedented fluorogenic mechanism based on a bent‐to‐planar conformational change in the S1 excited state. The S1 planarization induces an electronic configurational switch, almost quenching the inherent fluorescence (FL) of the peryleneimide moieties. However, the FL quantum yield is remarkably improved with a prolonged lifetime upon a slight environmental change. This fluorogenic function is realized by sensitive π‐conjugation design, as a more π‐expanded analogue does not show the planarization dynamics. With strong visible‐light absorption, the FL lifetime response synchronized with the flexible flapping motion is useful for the latest optical techniques such as FL lifetime imaging microscopy (FLIM). Abstract : A new member of the peryleneimide family, „flapping peryleneimide", shows an unprecedented fluorogenic mechanism. A bent‐to‐planar conformational change in S1 induces quenching of the inherent peryleneimide fluorescence (FL), while a slight environmental change resulted in a remarkable increase in the FL quantum yield and the FL lifetime.